BAG3 is a negative regulator of ciliogenesis in glioblastoma and triple‐negative breast cancer cells. Issue 1 (27th June 2021) - Linder, Benedikt; Klein, Caterina; Hoffmann, Marina E.; Bonn, Florian; Dikic, Ivan; Kögel, Donat
Abstract: By regulating several hallmarks of cancer, BAG3 exerts oncogenic functions in a wide variety of malignant diseases including glioblastoma (GBM) and triple‐negative breast cancer (TNBC). Here we performed global proteomic/phosphoproteomic analyses of CRISPR/Cas9‐mediated isogenic BAG3 knockouts of the two GBM lines U343 and U251 in comparison to parental controls. Depletion of BAG3 evoked major effects on proteins involved in ciliogenesis/ciliary function and the activity of the related kinases aurora‐kinase A and CDK1. Cilia formation was significantly enhanced in BAG3 KO cells, a finding that could be confirmed in BAG3‐deficient versus ‐proficient BT‐549 TNBC cells, thus identifying a completely novel function of BAG3 as a negative regulator of ciliogenesis. Furthermore, we demonstrate that enhanced ciliogenesis and reduced expression of SNAI1 and ZEB1, two key transcription factors regulating epithelial to mesenchymal transition (EMT) are correlated to decreased cell migration, both in the GBM and TNBC BAG3 knockout cells. Our data obtained in two different tumor entities identify suppression of EMT and ciliogenesis as putative synergizing mechanisms of BAG3‐driven tumor aggressiveness in therapy‐resistant cancers. Abstract : Here we describe a completely novel function of the co‐chaperone BAG3 as a negative regulator of ciliogenesis in glioblastoma and triple‐negative breast cancer. Our data obtained in these two different tumor entities identify suppression of ciliogenesis and epithelial to mesenchymal transition as putative synergizing mechanisms of BAG3‐driven tumor aggressiveness in therapy‐resistant cancers.